Analisis Perancangan Sistem Informasi Akuntansi Persediaan Barang Dagangan Guna Meningkatkan Pengendalian Internal Perusahaan (Studi Kasus Pada PT. Rejo Mulyo Plastik) - Rachmawati, Dewi; Rahman, Arief; Mahsina (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2023)
Effective inventory management is crucial for the sustainability of a company, as it involves not only logistical planning but also strict physical and administrative management. The objective of this research is to conduct an in-depth analysis of the implementation of the inventory accounting information system for trading goods at PT. Rejo Mulyo Plastik. This study employs a qualitative descriptive analysis approach. The results indicate that the existing systems and procedures are fairly adequate; however, the company still faces challenges in monitoring the issuance of goods. Since management is often not present, the process of issuing goods may not adhere to the established procedures. This highlights the importance of management's role in ensuring that everything operates according to the rules. To enhance oversight, the company needs to add more detailed documentation for each process of goods issuance.